THE ROLE OF THE STATE IN A MARKET ECONOMY: THEORETICAL APPROACHES AND PRACTICAL EXPERIENCE (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
This scientific article analyzes the role and functions of the state in a market economy from both theoretical and practical perspectives. It discusses the necessity and limits of state intervention based on classical, neoclassical, and Keynesian approaches. The study also examines international experience of developed and developing countries.